PEMANFAATAN KOMUNIKASI DIGITAL DALAM PENYEBARLUASAN INFORMASI KEGIATAN RESES ANGOOTA LEGISLATIF PROVINSI SULAWESI SELATAN - Fatwa Ramadhan, Muh; Muttaqin Mustari , Andi; Zelfia, Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2022)
The current digital era by using digital communication media that includes social media and the like, can provide convenience in the process of disseminating information, such as during recess activities or ongoing recesses between legislators and constituents. The use of technology enables people to get what they want, including legislators who play the role of channeling information to constituents by conveying the program to be carried out, by utilizing social media as a tool for disseminating information from their recess activities. This aims to improve the performance of the legislature and legislative institutions of South Sulawesi Province, by building relationships and trust in the community this is an important thing for public agencies. The type of research used is descriptive kulaitatid research with data collection techniques in the form of observation, interviews, and documentation. This research lasted for 1 month and is located in the DPRD of South Sulawesi Province. The information in this study came from members of the DPRD Prov. South Sulawesi, sub-staff cooperation and aspirations of the Provincial DPRD. South Sulawesi. The results of the study, it can be concluded that the use of digital media technology by the legislature during recess activities has a good role in increasing the effectiveness of the performance of the legislature in delivering information to constituents, which in the 4.0 era currently the use of digital media technology is widely used among the community.